Guided Self-Help for Patients with Chronic Fatigue Syndrome Prior to Starting Cognitive Behavioural Therapy: a Cohort Study. Issue 5 (5th May 2017) - Ali, Sheila; Goldsmith, Kimberley; Burgess, Mary; Chalder, Trudie
Abstract : Background: Previous research suggests that minimal interventions such as self-help guidance can improve outcomes in patients with fatigue or chronic fatigue syndrome (CFS).Aims: The aim of the current study was to investigate whether self-help guidance could improve physical functioning, social adjustment and fatigue in a group of patients with CFS who were awaiting CBT at a clinic in secondary care.Method: Patients completed questionnaires at their initial assessment (baseline), immediately before beginning CBT (pre-treatment), and after their last session of CBT (end of treatment). The primary outcome was physical functioning, and the secondary outcomes were social adjustment and fatigue. Multi-level linear models were used to assess change over time after adjustment for gender and age.Results: Multi-level models revealed that from baseline to pre-treatment, patients showed statistically significant improvements in physical functioning, but there were no statistically significant improvements in fatigue or social adjustment. However, all the primary and secondary outcomes showed statistically significant changes after CBT.Conclusions: The findings of this study indicate that self-help guidance may be beneficial for patients with CFS who are awaiting CBT treatment or those who are unable to access specialist treatment in their local area.